Methylation of TMEM176A is an independent prognostic marker and is involved in human colorectal cancer development. Issue 7 (3rd July 2017) - Gao, Dan; Han, Yingjie; Yang, Yang; Herman, James G.; Linghu, Enqiang; Zhan, Qimin; Fuks, François; Lu, Zhi John; Guo, Mingzhou
ABSTRACT: Colorectal cancer (CRC) is the third most common malignancy and the fourth most common cause of cancer related death worldwide. This study was designed to find tumor suppressors involved in CRC development by performing RNA-seq. Eight CRC cell lines and 130 cases of primary CRC samples were used. RNA-seq, methylation-specific PCR (MSP), flow cytometry, transwell assays, and a xenograft mouse model were used. Reduction of TMEM176A expression was confirmed in human CRC cells by RNA-seq. TMEM176A was expressed in LS180 and SW620 cells, loss of TMEM176A expression was observed in LOVO, HCT116, RKO, and DLD1 cells, and reduced TMEM176A expression was found in HT29 and SW480 cells. Unmethylation of the TMEM176A promoter was found in LS180 and SW620 cells, whereas complete methylation was found in LOVO, HCT116, RKO, and DLD1 cells, and partial methylation was found in HT29 and SW480 cells. Promoter region methylation correlated with loss of/reduced expression of TMEM176A . Re-expression of TMEM176A was induced by 5-aza-2′-deoxycytidine. TMEM176A was methylated in 50.77% of primary colorectal cancers. Methylation of TMEM176A was associated with tumor metastasis ( P <0.05) and was an independent prognostic factor for 5-year overall survival (OS) according to Cox proportional hazards model analysis ( P <0.05). TMEM176A induced apoptosis and inhibited cell migration and invasion in CRC cells. TMEM176A suppressed CRC cell growth both in vitro and in vivo . Our results suggest that expression of TMEM176A is regulated by promoter region methylation. TMEM176A methylation is an independent prognostic marker for 5-year OS in CRC, and may act as a tumor suppressor in CRC.